Cash management: case study of Standard Chartered Bank in Malaysia / Nur Azri Azyan Bahrudin - Bahrudin, Nur Azri Azyan (2011)
This study tries to analyse the relationship between cash management system in Standard Chartered bank with cash collections and electronic banking. In a business anything done financially affects cash eventually. Cash is to a business is what blood is to a living body. A business cannot operate without its lifeblood cash, and without cash management, there may remain no cash to operate. Cash movement in a business is two-way traffic. It keeps on moving in and out of business. The inflow and outflow of cash never coincides. Important aspect which is unique to cash management is time dimension associated with the movement of cash. Cash is money that is easily accessible either in the bank or in the business. It is not inventory, it is not accounts receivable, and it is not property. Due to non-synchronicity of cash inflow and outflow, the inflow may be more than the outflow or the outflow may be more than the inflow at a particular point of time. This needs regulation. Hence, there is a dire need to control its movement through skilful cash management. The primary aim of cash management is to ensure that there should be enough cash availability when the needs arise, not too much, but never too little.